1991
DOI: 10.1128/jvi.65.12.6509-6515.1991
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis and transcriptional mapping of the Marek's disease virus gene encoding pp38, an antigen associated with transformed cells

Abstract: The gene encoding a Marek's disease virus (MDV) pp38 phosphoprotein has been identified, sequenced, and localized to the BamHI H fragment to the left of the putative MDV origin of replication. The open reading frame was defined by sequencing of a lacZ-pp38 fusion protein gene from a Agt 1 expression library. The entire open reading frame is 290 amino acids long and codes for a protein with a calculated molecular weight of 31,169, compared with the size of 38 kDa of the phosphorylated form estimated by sodium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
2

Year Published

1992
1992
2004
2004

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(42 citation statements)
references
References 41 publications
2
38
0
2
Order By: Relevance
“…4B). In contrast, the 1.8-kb MDV pp38 transcript (13,16) was found in the cytoplasmic RNA fraction, as expected (Fig. 4C).…”
Section: Detection Of the Msrs And 10-kb Rna In Mdv-induced Primary Lsupporting
confidence: 86%
“…4B). In contrast, the 1.8-kb MDV pp38 transcript (13,16) was found in the cytoplasmic RNA fraction, as expected (Fig. 4C).…”
Section: Detection Of the Msrs And 10-kb Rna In Mdv-induced Primary Lsupporting
confidence: 86%
“…After determining the nucleotide sequence of the left half of the BamHI H fragment, where the B antigen gene was reported to be localized, we could not find a single open reading frame which is long enough to encode the 44-kDa peptide reported by Sithole et al (57) as a precursor (data not shown). Very recently, Cui et al (15) identified the gene encoding pp38 of MDV on the BamnHI H fragment, where the B antigen gene was reported to be localized (57). These findings strongly support our identification of the gB homolog as the B antigen.…”
Section: Discussionsupporting
confidence: 87%
“…Length polymorphism of restriction fragments between oncogenic and nononcogenic strains, as well as attenuated strains obtained by serial in vitro passage, has prompted efforts to identify genes that may be associated with tumorigenicity (6,7,18,19,61). In an alternative approach, viral gene products expressed in MDV-transformed cells were identified by characterizing mRNAs or by cDNA cloning techniques (6,13,40,56,62) or by monoclonal antibodies (14,15,30,45). One property of MDVtransformed cells has made it extremely difficult to analyze potential tumor-associated transcripts unambiguously; a few cells in a tumor or in an established cell line in which the virus undergoes the lytic cycle will make the obtained data difficult to interpret.…”
Section: Six Cell Lines Derived Frommentioning
confidence: 99%